2009
DOI: 10.1002/rcm.4366
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the geographical origin of beefs being circulated in Korean markets based on stable isotopes

Abstract: We have examined the carbon, nitrogen and oxygen isotopic compositions of American, Mexican, Australian, New Zealand and Korean beefs, which are currently being circulated in Korean markets, to check whether stable isotope ratios can identify their country of origin. Each beef exhibited statistically distinct isotopic compositions, especially in oxygen and carbon, because of the different isotopic compositions of their water and cattle feeds. Nevertheless, their isotopic compositions still showed some overlap,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 16 publications
6
29
0
Order By: Relevance
“…Our results are consistent with other studies analysing beef samples from several parts of the world, which found high d 13 C values of Brazilian beef samples (Heaton et al, 2008;Nardoto et al, 2006;Schmidt et al, 2005). Previously published studies also found high d 13 C values (À14.3‰ to À9.5‰) for US beef samples (Bong et al, 2010;Heaton et al, 2008;Horacek & Min, 2010;Nakashita et al, 2008;Schmidt et al, 2005); and for patties from US fast-food chains (Chesson et al, 2008). The lower d 13 C values observed in Big Mac Ò patties from European countries were also observed in beef sampled from that continent (Heaton et al, 2008;Schmidt et al, 2005).…”
Section: Comparison Between Isotopic Values Of Big Mac ò Patties In Dsupporting
confidence: 96%
See 1 more Smart Citation
“…Our results are consistent with other studies analysing beef samples from several parts of the world, which found high d 13 C values of Brazilian beef samples (Heaton et al, 2008;Nardoto et al, 2006;Schmidt et al, 2005). Previously published studies also found high d 13 C values (À14.3‰ to À9.5‰) for US beef samples (Bong et al, 2010;Heaton et al, 2008;Horacek & Min, 2010;Nakashita et al, 2008;Schmidt et al, 2005); and for patties from US fast-food chains (Chesson et al, 2008). The lower d 13 C values observed in Big Mac Ò patties from European countries were also observed in beef sampled from that continent (Heaton et al, 2008;Schmidt et al, 2005).…”
Section: Comparison Between Isotopic Values Of Big Mac ò Patties In Dsupporting
confidence: 96%
“…The lower d 13 C values observed in Big Mac Ò patties from European countries were also observed in beef sampled from that continent (Heaton et al, 2008;Schmidt et al, 2005). The large variance we observed in the d 13 C values of Big Mac Ò patties from Australia (Table 1) was also observed in beef samples from this country (Bong et al, 2010;Heaton et al, 2008;Horacek & Min, 2010;Nakashita et al, 2008).…”
Section: Comparison Between Isotopic Values Of Big Mac ò Patties In Dsupporting
confidence: 74%
“…Using the predicted tap water oxygen isotope ratio (d 18 O we ) of the location (Bowen et al 2007 Tracing the geographical origin of beef has recently been recognized as a food-safety concern in Europe and Asia. Preliminary data suggest the stable isotope analysis of beef may be useful to answer questions of region-of-origin (Nakashita et al 2008;Bong et al 2010;Horacek and Min 2010). A recent survey of beef raised in Japan published by Nakashita et al (2008) …”
Section: Supermarket Beef Cattle Eatmentioning
confidence: 96%
“…The elemental analyzer was based on the Dumas principle, in which dynamic flash combustion is followed by packed gas chromatography column separation of the gaseous species produced (e.g. N 2 , CO 2 and SO 2 ) [24]. Isotopic ratios are expressed in delta (δ) notation in parts per thousand (‰) relative to the accepted international standards: Vienna Pee Dee Belemnite (PDB) for carbon isotopes and atmospheric air for nitrogen isotopes.…”
Section: Stable Isotopic Analysismentioning
confidence: 99%